Zikir sebagai Solusi dalam Perspektif al-Qur’an - Abdul Ghoni (Ulumul Qur'an: Jurnal Kajian Ilmu Al-Qur'an dan Tafsir, 2021)
There is a global big problem during coronavirus pandemic during 2020. This problem causes many aspects of human life. There are many people who experiences feeling of stress and anxiety. The physical impact of this pandemic is so huge, but also the psychic impact of it is bigger than it. Being hopeless is not a solution, but it will increase the existed problem. Therefore, it will be very urgent to find out the way how to solve and face the difficulty kindly. Among the solution is the Islamic value in al-Qur’an. One of the strategic solutions is by remembering Allah all the day in all conditions. Implicitly by remembering Allah can bring the human to the way out of the problem. It’s caused that remembering Allah will bring peace and calmness. Through the calm condition, everyone can see the problem wisely and gradually can solve the problem.